Traditional Uses, Chemical Constituents, and Biological Activities of Bixa orellana L.: A Review - Daniela de Araújo Vilar; Marina Suênia de Araujo Vilar; Túlio Flávio Accioly de Lima e Moura; Fernanda Nervo Raffin; Márcia Rosa de Oliveira; Camilo Flamarion de Oliveira Franco; Petrônio Filgueiras de Athayde-Filho; Margareth de Fátima Formiga Melo Diniz; José Maria Barbosa-Filho (The Scientific World Journal)
Bixa orellana L., popularly known as “urucum,” has been used by indigenous communities in Brazil and other tropical countries for several biological applications, which indicates its potential use as an active ingredient in pharmaceutical products. The aim of this work was to report the main evidence found in the literature, concerning the ethnopharmacology, the biological activity, and the phytochemistry studies related to Bixa orellana L. Therefore, this work comprises a systematic review about the use of Bixa orellana in the American continent and analysis of the data collected. This study shows the well-characterized pharmacological actions that may be considered relevant for the future development of an innovative therapeutic agent.